(untitled) (Acta Scientiarum. Biological Sciences, 2012)
This study was carried out in the Serra de Itabaiana National Park from October, 2006, to October, 2007. The main objective was to quantify litterfall production and analyze decomposition rates in a tropical seasonal semideciduous forest. Forty 0.25 m² collectors were used to quantify the litterfall and 36 litterbags to record the rate of decomposition of the foliar biomass. The total litterfall production was 8.6 ton ha-1 in 11 months, of which 54.6% of leaves. The constant of leaf decomposition (K) was 0.52, and the half-life of the leaf biomass was estimated to be 495 days. A significant correlation was observed between leaf fall and monthly precipitation, but no relationship was found between decomposition rates and rainfall.